CORRELATION OF PARENTING PATTERNS WITH THE RISK OF OBESITY IN ADOLESCENTS IN SMK IT RAFLESIA DEPOK - Nourmayansa Vidya Anggraini; Angel Sri Yuliningtias; Diah Ratnawati; Ritanti Ritanti (Indonesian Journal of Community Health Nursing, 2022)
Introduction: Obesity is a condition when an individual is overweight beyond normal weight. Adolescents have a risk of obesity which may occur into adulthood that it can have a negative impact on the development of adolescents both physically and psychologically. Parental feeding management has a significant relationship with adolescent food quality. This study aims to determine the relationship between parenting patterns with the risk of obesity in adolescents at SMK IT Raflesia Depok. Method: The method used was an observational quantitative research with analytic design and using a cross sectional study approach. The sample used was 102 samples obtained through the Stratified Random Sampling technique. Measurements were made using height and weight measurements and filling out a questionnaire using a structured instrument. Results: The results of the analysis with the chi square test showed that there was a relationship between parenting pattern with the risk of obesity in adolescents with p value = 0.018 (<0.05). Conclusion: Parenting in accordance with the development of adolescence must also be considered for parents in an effort to overcome the risk of obesity. Keywords: adolescence; obesity risk; parenting patterns